Correlation of in-situ transmission electron microscopy and microchemistry analysis of radiation-induced precipitation and segregation in ion irradiated advanced ferritic/martensitic steels. (15th March 2019) - Zheng, Ce; Ke, Jia-Hong; Maloy, Stuart A.; Kaoumi, Djamel
Abstract: This article presents a novel method combining ion irradiation, in-situ transmission electron microscopy (TEM), and microchemistry analysis before/after irradiation, which allows to examine same microstructural areas throughout ion irradiation. A 12 wt% Cr Ferritic/Martensitic steel (HT9) was irradiated in the TEM to 1.17 × 10 20  ions·m −2 at 440 °C using 1 MeV Kr 2+ ions, and the in-situ characterization focused on radiation-induced precipitation and segregation. Results of in-situ experiments were compared with those obtained from ex-situ experiments, to showcase how this method helps to better understand precipitation kinetics in the irradiated material examined ex-situ, for which only snapshots are available at limited doses. Graphical abstract: Unlabelled Image